Larrea tridentata (DC.) Coville Leaf Extracts Inhibit the Bacterial Triggers of Some Autoimmune Inflammatory Diseases - Zyl, Rebecca Van; Cock, Ian Edwin (Pharmacognosy Communications)
Background: Larrea tridentata leaves are used traditionally to treat bacterial infections and inflammation. Despite the traditional uses, relatively few studies have examined the ability of L. tridentata leaf extracts to inhibit the growth of the bacterial triggers of autoimmune inflammatory diseases. Materials and Methods: Larrea tridentata extracts were screened for growth inhibitory activity against bacterial triggers of selected autoimmune inflammatory diseases and the activity was quantified using disc diffusion and liquid dilution MIC assays. Toxicity was evaluated using the Artemia nauplii cytotoxicity assay. Results: Larrea tridentata extracts strongly inhibited the growth of several bacterial triggers of autoimmune diseases, although they were ineffective inhibitors of A. baylyi growth. The methanolic and ethyl acetate extracts were particularly good inhibitors of Proteus spp. and Klebsiella pneumoniae growth, with LD MIC values between 32 and 375 μg/mL. The methanolic and ethyl acetate extracts were also particularly good inhibitors of Streptococcus pyogenes (LD MICs 63-125 μg/mL). None of the L. tridentata extracts were toxic in the ALA toxicity assay. Conclusion: Larrea tridentata leaf extracts inhibit the growth of some bacterial triggers of rheumatoid arthritis, ankylosing spondylitis, multiple sclerosis and rheumatic fever. Further in vivo studies to determine the anti-inflammatory and antibacterial mechanisms are warranted.
Keywords: Chaparral; Creosote bush; Antibacterial activity; Rheumatoid arthritis; Ankylosing spondylitis; Multiple sclerosis; Rheumatic fever; Lignin.